Protocol for using mixed methods and process improvement methodologies to explore primary care receptionist work - Litchfield, Ian (BMJ Open, 2016)
INTRODUCTION: The need to cope with an increasingly ageing and multimorbid population has seen a shift towards preventive health and effective management of chronic disease. This places general practice at the forefront of health service provision with an increased demand that impacts on all members of the practice team. As these pressures grow, systems become more complex and tasks delegated across a broader range of staff groups. These include receptionists who play an essential role in the successful functioning of the surgery and are a major influence on patient satisfaction. However, they do so without formal recognition of the clinical implications of their work or with any requirements for training and qualifications. METHODS AND ANALYSIS: Our work consists of three phases. The first will survey receptionists using the validated Work Design Questionnaire to help us understand more precisely the parameters of their role; the second involves the use of iterative focus groups to help define the systems and processes within which they work. The third and final phase will produce recommendations to increase the efficiency and safety of the key practice processes involving receptionists and identify the areas and where receptionists require targeted support. In doing so, we aim to increase job satisfaction of receptionists, improve practice efficiency and produce better outcomes for patients. ETHICS AND DISSEMINATION: Our work will be disseminated using conferences, workshops, trade journals, electronic media and through a series of publications in the peer reviewed literature. At the very least, our work will serve to prompt discussion on the clinical role of receptionists and assess the advantages of using value streams in conjunction with related tools for process improvement.